“Academic Writing” – an Ironical Expression in the History of Culture: Array - Munteanu, Cristinel (Acta Universitatis Danubius. Communicatio, 2020)
In this article I aim at analyzing the evolution of the terms academy and academic, starting with their etymology, in order to emphasize a bizarre cultural fact. Taking into account both their Greek origin and a sense of linguistic consciousness specific to some speakers, one could characterize the expression “academic writing” (referring to a certain discipline/course taught in our universities) as an ironical formula in the history of culture, since, originally, Plato’s Akademia and ‘writing’ in itself had nothing in common. On the contrary, Plato was against writing in general, as proved by some quotations excerpted from his works.